Guidelines for learning and teaching of final year engineering projects at AQF8 learning outcomes - Rasul, M.; Lawson, L.; Jarman, R.; Howard, P.; Hadgraft, R.; Fae, M.; Kestell, C.; Anwar, Faisal; Stojcevski, A.; Alan, H.; Kootsookos, A. (2015)
Final Year Engineering Projects (FYEP) present students, academic staff (project supervisors) and assessors (review panel), professional accreditation bodies and industry project sponsors with many challenges. Experience with coordinating and examining FYEPs and discussions with colleagues at past few AAEE conferences indicated that many engineering educators have concerns about learning and teaching approaches of FYEPs. Development of good practice guidelines which meet Australian Qualifications Framework (AQF) Level 8 outcomes was therefore required. This led to a successful Australian Government grant on “Assessing Final Year Engineering Projects (FYEPs): Ensuring Learning and Teaching Standards and AQF8 Outcomes” funded by Office for Learning and Teaching.